THORIUM LINES IN THE SPECTRA OF SEVERAL SMC SUPERGIANT STARS - Gopka, V. F.; Vasil’eva, S. V.; Yushchenko, A. V.; Andrievsky, S. M. (Одеські астрономічні публікації, 2007)
We present the results of identifications of the Th II lines in the spectra of four stars in the Small Magellanic Cloud: PMMR 23, PMMR 39,PMMR144, and PMMR 145. We report about detection of the lines of Th II in the visible part of spectra of K-supergiants. Thorium lines in the spectra of these stars are stronger than the thorium lines in the spectra of HD221170 and Arcturus. The thorium abundances in the atmospheres of four SMC stars are scattered from +0.05 to -0.69 in the scale where logN(H)=12.